2015
DOI: 10.1089/sur.2014.209
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring Neutrophil-Expressed Cell Surface Esophageal Cancer Related Gene-4 after Severe Burn Injury

Abstract: Background: We identified recently esophageal cancer related gene-4 (ECRG4) as a candidate cytokine that is expressed on the surface of quiescent polymorphonuclear leukocytes (PMNs) and shed in response to ex vivo treatment with lipopolysaccharide. To investigate the potential biologic relevance of changes in cell surface ECRG4 in human samples, we performed a pilot study to examine a population of burn patients in whom blood could be analyzed prospectively. We hypothesized that cutaneous burn injury would alt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…6E and 5, G and I) and restores homeostatic expression levels. This model is further supported by studies of human burn patients, where it has been observed that cell surface ECRG4 on circulating leukocytes diminishes after injury but returns to housekeeping levels as patients recover (24). These findings support a role for ECRG4 as a sentinel factor, which can both precondition the responsiveness of leukocytes through its regulation of CD44 expression and respond to environmental cues to mediate the kinetics of the cutaneous inflammatory response.…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…6E and 5, G and I) and restores homeostatic expression levels. This model is further supported by studies of human burn patients, where it has been observed that cell surface ECRG4 on circulating leukocytes diminishes after injury but returns to housekeeping levels as patients recover (24). These findings support a role for ECRG4 as a sentinel factor, which can both precondition the responsiveness of leukocytes through its regulation of CD44 expression and respond to environmental cues to mediate the kinetics of the cutaneous inflammatory response.…”
Section: Discussionmentioning
confidence: 54%
“…In murine tumor models, the ability of soluble ECRG4 to increase the recruitment of inflammatory cells is dependent on thrombin cleavage (17). In humans with severe burn injury, ECRG4 is shed from circulating neutrophils, while restoration of cell surface ECRG4 expression correlates with recovery (24). These observations suggest that ECRG4 has a role in regulating specific inflammatory responses, although its function in injury has not been determined in ECRG4 knockout (KO) mice.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation